Research on the Path of Empowering Mathematics Basic Education with Artificial Intelligence - Zhou, Ya’nan; Chang, Yonghu (Journal of Research in Vocational Education, 2025)
With the rapid development of technology, artificial intelligence has gradually penetrated into the field of education, bringing new opportunities and challenges to mathematics basic education. This article takes mathematics basic education as the starting point to explore the path and practice of empowering mathematics basic education with artificial intelligence. Covering aspects such as leadership attention, system support, teacher leadership, student centeredness, parental understanding, and project guidance, the aim is to fully leverage the advantages of artificial intelligence through multi-party collaboration, and improve the quality of mathematics teaching and student learning outcomes.